2008
DOI: 10.1253/circj.72.1092
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Carotid Plaque Vulnerability Using Structural and Geometrical Determinants

Abstract: upture of atheromatous plaque in the carotid artery often leads to thrombosis and subsequent stroke. 1 This is potentially preventable by carotid revascularization techniques, and the degree of luminal stenosis is commonly used in clinical practice as an indicator for carotid endarterectomy or carotid artery angioplasty/stenting. Carotid endarterectomy has been shown to be beneficial in patients with symptomatic high-grade (70-99%) stenosis, 2,3 but it is more difficult to draw conclusions about possible benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 34 publications
(42 reference statements)
3
30
0
1
Order By: Relevance
“…The result obtained from 30 patients using 2D structure-only modelling indicated that the stress level in symptomatic individuals was about twice as high as that of the asymptomatic cohort. This observation was further confirmed by a study with a slightly larger patient cohort 55 (n 5 40). Sadat et al 56,57 and Zhu et al 58 found that stress level right after the onset of symptom was much higher than that of recently symptomatic and asymptomatic patients.…”
Section: Carotid Plaque Biomechanical Analysis Using Mr Imagingsupporting
confidence: 57%
“…The result obtained from 30 patients using 2D structure-only modelling indicated that the stress level in symptomatic individuals was about twice as high as that of the asymptomatic cohort. This observation was further confirmed by a study with a slightly larger patient cohort 55 (n 5 40). Sadat et al 56,57 and Zhu et al 58 found that stress level right after the onset of symptom was much higher than that of recently symptomatic and asymptomatic patients.…”
Section: Carotid Plaque Biomechanical Analysis Using Mr Imagingsupporting
confidence: 57%
“…28 Li et al have demonstrated the importance of the detection of the vulnerable plaques. 29 These and many other studies highlight the importance of the simple and reliable predictors of atherosclerosis like ELC for the detection of the atherosclerotic changes as early as possible. Identification of the persons at risk of such major outcomes in the earlier stages would lower the burden of morbidities and mortalities associated with these disorders.…”
Section: Discussionmentioning
confidence: 94%
“…[41][42][43] Plaque is formed by inflammation, oxidation, and endothelial dysfunction as a late response compared with thickening of the intimamedia. [44][45][46][47][48] When the entire study population (4,088), including subjects with hypertension, diabetes, and dyslipidemia, were included in the analysis, the relationship between MetS and carotid plaques was significant in both men (OR 1.45, 95%CI 1.16-1.81) and women (OR 1.65, 95%CI 1.36-1.99). Additional prospective investigations are needed to further examine the sex differences in the relationship between MetS and subclinical atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%